Viral Infections and Cutaneous Drug-Related Eruptions - Eleonora Anci; Camille Braun; Camille Braun; Annalisa Marinosci; Frédérique Rodieux; Elise Midun; Elise Midun; Maria-Jose Torres; Jean-Christoph Caubet (Frontiers Media S.A., 2021)
In the general population, up to 10% of children treated by antibiotics have cutaneous adverse drug reaction, but allergy is confirmed in less than 20% of patients. Most of the non-allergic reactions are probably due to virus, such as enterovirus acute infection or Ebstein-Barr Virus (EBV) acute infection or reactivation. Especially in children, viruses have the propensity to induce skin lesions (maculopapular rash, urticaria) due to their skin infiltration or immunologic response. In drug-related skin eruptions, a virus can participate by activating an immune predisposition. The culprit antibiotic is then the trigger for reacting. Even in severe drug-induced reactions, such as Drug Reaction with Eosinophilia and Systemic Symptoms (DRESS) syndrome, viruses take part in immune phenomena, especially herpes viruses. Understanding the mechanisms of both virus- and drug-induced skin reaction is important to develop our clinical reflection and give an adaptive care to the patient. Our aim is to review current knowledge on the different aspects and potential roles of viruses in the different type of drug hypersensitivity reactions (DHR). Although major advances have been made those past year, further studies are needed for a better understanding of the link between viruses and DHR, to improve management of those patients.